Analysis of level of detail as game optimization method in Mobile Legend’s character - Eveline Dau Leja; M. Alif Wicaksono; M. Garry Saputra; Rista Indri Yuliana (Deskomvis: Jurnal Ilmiah Desain Komunikasi Visual, Seni Rupa dan Media, 2025)
Game is one of the entertainments that is sought after by people. Every game has given performance experience for its player that need to be well designed to reduce any issue. Optimization is essential for every game player to avoid any technical issue, including low frame rates and high battery consumption. One of the optimization methods is called Level of Detail (LOD). For this article, Mobile Legends is chosen as the topic. Mobile Legends is a Multiplayer Online Battle Arena game that used a real-time rendering that relies on the performance adjustment. Mobile games like Mobile Legends could benefit from implementing LOD. The goal of this article is to show the relation between LOD framework such as shader and Mobile Legend in-game settings. The method used is qualitative experiment research with game screenshots. Based on experiment, there are new analysis based on the proposed ideas. A combined framework is possible to be implemented to one type of the game visual settings